SOLA IUSTITIA - Rudiyanto Rudiyanto (Sekolah Tinggi Theologia Abdiel, 2018)
Capitalism seems to be the result of 500 years of Prostentantism reformation. By unraveling some bads conditions of the world today as presence of “powers” as reflected in the New Testament, and by believing that Protestantism reformation still has power in its spirits: ad fontes and semper reformanda, this article shows that we are able to put forward an intrinsic adagium of Protestantism reformation beside of sola gratia, sola fide, and sola scriptura; namely sola iustitia.